Diagnóstico de hemofilia mediante la determinación de factores de la coagulación en pacientes con antecedentes genéticos. - Guaranga Lema, Rosa Elena (2022)
ABSTRACT: The diagnosis of hemophilia through the determination of coagulation factors in patients with a genetic background, developing to highlight the different types of hemophilia through a documentary, non-experimental design, and descriptive level, using scientific sources related to the subject of study, bibliographic reviews, books, electronic journals, and medical guides. At the same time, it was cross-sectional because the research is conducting in a specific period. It was retrospective since the bibliographic data was analyzed in publications according to the topic with a population of 89 articles. A sample of 35 scientific articles was extracted that met the inclusion criteria and contained results to compare with the stated objectives. Identify the patient's main characteristics among the main effects, such as hemorrhages, joint pain, hemarthrosis, and skin hematomas. In addition to genetic background and associated pathologies, it was determined that the leading carriers of the pathology were grandparents, parents, and uncles. To detect disease, TP tests, TTPa, complete blood count, and complementary molecular tests were utilized. It is concluded that patients with hemophilia present bleeding and hematomas as the primary symptom, while genetic antecedents in most cases are not recorded. However, those who did record that they present this pathology mention relatives up to the third generation; using the previous tests, the types of hemophilia suffered by the patient are identified.